Stock Market Proxy Testing in Beta Calculation in the COVID-19 Pandemic Period on the Indonesia Stock Exchange - Yuvica Lara Rovantiane Adicondro; Robiyanto Robiyanto; Samuel Martono (University of Merdeka Malang, 2023)
This study was conducted to assess the stock price index on the Indonesia Stock Exchange (IDX) which can be used as a proxy for the stock market in Indonesia. The indexes used to search for stock market proxies in Indonesia are JCI, IDX30, LQ45, IDX BUMN20, Jakarta Islamic Index (JII), KOMPAS100, MNC36, SRI-KEHATI, and PEFINDO25. The period in this study is from June 2018 to October 2021 obtained through bloomberg.com. Based on the results of the Paired Sample t-Test, the JCI returns before and during the Covid-19 pandemic did not show a difference in stock beta. Then, the results of the Standard Error Estimate (SEE) test show that JCI returns have the smallest deviation rate in the period when Covid-19 occurred and in the entire period. The results showed that the JCI return can be used as a proxy for the stock market in Indonesia compared to the returns of other stock indexes.